Optimisation of Russian railways’ high-speed routes in the regions - A. A. Bychkova (Вестник университета, 2022)
Rail transport is constantly in development and improvement, as it is one of the most important strategic means of transportation. That is why the optimization of Russian railway routes in this case is an integral element of development. The introduction of a high-speed passenger transportation route makes it possible to increase throughput capacity, improve service conditions, and strengthen the position in the industry. The article points out the necessity of optimising the route from the Ural to the Volga federal districts. The relevance of the topic under study lies in the advantage of railway transport in interspecific competition in the market for the provision of passenger transportation services. The author used the local Moran index in the analysis, studied regional interconnections, and identified clusters. The results of the study are visually represented in the figure, where the dotted line highlights the potential route of high-speed traffic Yekaterinburg–Kazan. The article describes the possible risks of implementing this route, cites optimization expediency factors (increase of interspecific competition).